2010
DOI: 10.4321/s0004-05922010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Water restriction in goats during hot-dry season in the humid tropics: feed intake and weight gain

Abstract: SUMMARYTwelve non-pregnant female goats (West African Dwarf, WAD and Red Sokoto, RS) were used to investigate the effect of volumetric (0%, 33% and 67%) water restriction on feed intake and weight gain over a period of eight weeks. The goats are of 2 age groups: younger and older than 1 year. The experiment was arranged in a modified cross-over design with three treatment periods of 1 week each. In-between each treatment period was a 2-week wash-out period, when the effect of the previous was expected to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
3
11
0
1
Order By: Relevance
“…Imposition of water restriction enforced the animals to use different strategies, which applied much more economic use of water for maintaining the water balance and thermoregulation, and this switch was reflected by marked reduction in the water-to-feed intake ratio. A Similar sharp reduction in the ratio between water and feed intake in response to water restriction was also found by Ahmed and El Kheir (2004) in the Sudanese desert goats and Abioja et al (2010) in the West African tropical goats.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Imposition of water restriction enforced the animals to use different strategies, which applied much more economic use of water for maintaining the water balance and thermoregulation, and this switch was reflected by marked reduction in the water-to-feed intake ratio. A Similar sharp reduction in the ratio between water and feed intake in response to water restriction was also found by Ahmed and El Kheir (2004) in the Sudanese desert goats and Abioja et al (2010) in the West African tropical goats.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, in the present experiment, the reduction in FFI upon restricting FWI was proportionally much lower than the level of water restriction imposed. Similar moderate reduction in feed intake in proportion to considerable imposition of water restriction (33% and 67%) was found in breeds of tropical (Abioja et al, 2010) and desert goats (Alamer, 2009). In cows, with 50% drinking water restriction, the reduction in feed intake was 20% lower than that during when water was available ad libitum (Burgos et al, 2001).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The values of this research to both Azul and Graúna were higher than the recommended by NRC (2007), which mentions that there must be a relation between dry matter and water consumption, which in this experiment should have a mean of 1.52 liters. ABIOJA et al (2010) reported that there is a positive correlation between the food and water consumption, and in the present study it may be observed that the Moxotó goats consumed less dry matter and water in relation to other animals. This high water consumption may also be explained by the type of food provided, which had a roughage: concentrate ratio of 47:53, and a high percentage of energy in the diet increases the water consumption ARAÚJO et al, 2010), but also to the environment where the animals were housed, subjected to high temperatures and low relative humidity (Table 1).…”
Section: Shade Watersupporting
confidence: 55%
“…It is also the most abundant substance in living systems (NRC, 2007), and the percentage of water in the body of goats depends on the alimentation, the age of the animal and the amount of fat, protein and ash present in their bodies (ALVES et al, 2008;DIAS et al, 2008;ARAÚJO et al, 2010). Water requirements for goats vary with the seasons, air temperature, weight, stage of production, type and food intake (ABIOJA et al, 2010), and the animals at elevated temperatures increase water intake, and thus this must be offered to the animals on tropical climate in sufficient quantity and desirable quality (BRASIL et al, 2000;NRC, 2007), aiming to replace losses through perspiration and respiration, besides possible body cooling, through the water contact, colder than the body, with the mucous membranes of the digestive tract, and replace losses through urine, feces and in the milk production.…”
Section: Introductionmentioning
confidence: 99%